Integrating local environmental observations and remote sensing to better understand the life cycle of a thermokarst lake in Arctic Alaska. Issue 1 (31st December 2023) - Jones, Benjamin M.; Schaeffer Tessier, Susan; Tessier, Tim; Brubaker, Michael; Brook, Mike; Schaeffer, Jackie; Ward Jones, Melissa K.; Grosse, Guido; Nitze, Ingmar; Rettelbach, Tabea; Zavoico, Sebastian; Clark, Jason A.; et al.
ABSTRACT: On 29 June 2022, local observers reported the drainage of a 0.5 ha lake near Qikiqtaġruk (Kotzebue), Alaska, that prompted this collaborative study on the life cycle of a thermokarst lake in the Arctic. Prior to its drainage, the lake expanded from 0.13 ha in 1951 to 0.54 ha in 2021 at lateral rates that ranged from 0.25 to 0.35 m/year. During the drainage event, we estimate that 18, 500 m 3 of water drained from the lake into Kotzebue Sound, forming a 125-m-long thermo-erosional gully that incised 2 to 14 m in ice-rich permafrost. Between 29 June and 18 August 2022, the drainage gully expanded from 1 m to >10 m wide, mobilizing 8, 500 m 3 of material through erosion and thaw. By reconstructing a pre-lake disturbance terrain model, we show that thaw subsidence occurs rapidly (0.78 m/year) upon transition from tundra to lake but that over a seventy-year period it slows to 0.12 m/year. The combination of multiple remote sensing tools and local environmental observations provided a rich data set that allowed us to assess rates of lake expansion relative to rates of sub-lake permafrost thaw subsidence as well as hypothesizing about the potential role of beavers in arctic lake drainage.